Pelatihan dan Pendampingan Digitalisasi Inventaris Alat Praktikum Berbasis Web di SMK Manangga Pratama - Teuku Mufizar; Evi Dewi Sri Mulyani; Arifubila Ramadhani Sigand; Dika Marasidik; Ihsan Musyaffa; Ahmad Sobirin; Taqi Muhammad (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
The management of laboratory equipment in the Light Vehicle Engineering (TKR) department at SMK Manangga Pratama was previously done manually, which is vulnerable to recording errors and difficulties in monitoring tool stock. This community service activity aims to provide training and mentoring for the digitalization of inventory management through the implementation of a web-based Practicum Lab Equipment Information System (BengkelTrack). The implementation method includes requirements analysis, system development, testing, installation, and hands-on training for laboratory admins and the Principal. The result of this activity is the implementation of a digital inventory application featuring tool data management, borrowing, transaction history, and automatic report generation. Through mentoring, partners showed high enthusiasm and independence in operating the system. In conclusion, the implementation of this system has proven to facilitate the performance of teachers and staff in documenting assets in real-time and assists the Principal in monitoring the availability of practical facilities. As a follow-up recommendation, regular system maintenance and the development of mobile-friendly features are suggested to increase monitoring flexibility.